Antibacterial Potency of Bioactive Compounds from Areca catechu Nuts: A Molecular Docking Study Targeting 8H1B - Mariska, Soraya; Rahmadi, Muhammad Zaki Ammar; Hanifa, Milla; Hasna, Naurah Rosyidah; Irawan, Siti Azara Nayla; Putri, Refsya Azanti; Saputra, Muhammad Yogi (Universitas Pakuan, 2024)
Areca catechu, a plant in the Arecaceae family, is rich in bioactive secondary metabolite compounds. Areca catechu has many benefits and potentials, including its antibacterial properties. This study aims to describe the potential of secondary metabolite compounds as antibacterials targeted at 8H1B and their toxicity profile through in silico analysis. The ligands used in this study were catechin, acatechu B, jacareubin, clindamycin as a comparison compound, and S-adenosylmethionine as a native ligand. The results showed that acatechu B had the lowest binding energy (-12.66 kcal/mol) compared to catechin (-9.44 kcal/mol), jacareubin (-8.99 kcal/mol), clindamycin (-10.93 kcal/mol), and S-adenosylmethionine (-11.76 kcal/mol). According to Biovia Discovery simulations, the Areca catechu bioactive compound interacts with 8H1B through van der Waals, conventional hydrogen bonds, and different variants of pi interaction. The toxicity profiles of the Areca catechu bioactive compound showed that they were not hepatotoxic, not mutagenic, not carcinogenic, and had safe LD50 values. These results suggest that the Areca catechu bioactive compound possesses antibacterial potential by targeting 8H1B.